2013
DOI: 10.1002/mus.23867
|View full text |Cite
|
Sign up to set email alerts
|

High resolution ultrasound in posterior interosseous nerve syndrome

Abstract: High-resolution ultrasound allows for differentiation between patients with PIN syndrome and healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
1
43
0
3
Order By: Relevance
“…Ultrasonography is a reliable method for the evaluation of the nerves of the elbow [1][2][3] and of the structures that may cause its compression [4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography is a reliable method for the evaluation of the nerves of the elbow [1][2][3] and of the structures that may cause its compression [4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…The posterior interosseous nerve may be compressed between the superficial and deep portions of the supinator muscle during pronation-supination of the elbow [8] (Fig. 5).…”
Section: Structures Potentially Associated With Nerve Compressionmentioning
confidence: 99%
“…In either case, nerve US has been shown to be a useful diagnostic tool that shows increased size (CSA and diameter) and loss of fascicular structure with reduced echogenicity of the PIN. 7 Our results show that US found that half of the patients with radial nerve damage at the site of trauma have evidence of PIN involvement. In our opinion this finding is consistent with a second site of pathology, but the clinical relevance, prognostic implications, and possible treatment still need to be clearly assessed.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that when PINs are found to be compressed at the arcade of Fröhse, they show a proximal swelling to up to 2 to 3.3 mm, compared with 1.1 to 1.3 mm in healthy subjects. 4,5 However, considerable statistical error exists while measuring PIN diameter because of its small size and its normally tapering shape. 6 In our case, the PIN did not show marked swelling, but there was obvious compression and angulation by the superficial head of the supinator muscle.…”
mentioning
confidence: 99%
“…7 Ultrasonography may assist in localizing the exact site of compression and excluding external compression by secondary causes. 5 Furthermore, real-time hydrodissection can be performed accurately to relieve the compression.…”
mentioning
confidence: 99%